Perpindahan Pemeliharaan Anak yang belum Mumayyiz Kepada Ayah Menurut Kompilasi Hukum Islam : (Studi Putusan No. 1882/Pdt.G/2019/PA.Mdn) - Ubaidillah Ibnu Mas’ud (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study examines the transfer of custody (hadhanah) rights of a non-mumayyiz child to the father, as decided in Judicial Decision No. 1882/Pdt.G/2019/PA.Mdn by the Medan Religious Court. According to Article 105 letter (a) of the Compilation of Islamic Law (KHI), the custody of a child under the age of 12 (non-mumayyiz) is generally granted to the mother. However, in this case, the court ruled otherwise. The focus of this research is to analyze the legal reasoning and judicial considerations behind this deviation from normative provisions. This is a normative legalresearch employing a juridical and conceptual approach. Primary data include statutory provisions and the official court ruling, while secondary data are derived from classical Islamic jurisprudence, modern legal commentaries, and related literature. The analysis uses descriptive-analytical methods to examine the legal basis, fiqh arguments, and the principle of maslahah al-mahdhun (best interests of the child). The findings indicate that the court transferred custody to the father on the grounds that the mother had remarried and was experiencing psychological instability, which could endanger the child’s well-being. The decision was based on Article 156 letter (c) of the KHI, which allows custody to be transferred if the mother fails to guarantee the child’s physical and mental safety. The judge also considered the father's financial capability, emotional stability, and supportive environment as decisive factors in ensuring the child's best interests. This research concludes that child custody in Islamic law is flexible and adaptive, prioritizing the child’s welfare over formal legal entitlements. It also highlights the role of religious court jurisprudence in aligning Islamic legal norms with contemporary social realities.